1999
DOI: 10.1017/s0790966700005188
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits in parents of people with autism

Abstract: Objectives: This study set out to explore if there were measurable personality characteristics specific to parents of people with autism.Method: Parents of 12 people with a DSM-III-R diagnosis of autism presented for the study. Each of the people with autism were matched where possible with a counterpart without autism but with a lifelong disability on parameters of age, sex and IQ level. Parents of the ‘autism’ and ‘non-autism’ groups were then interviewed in detail using four personality assessment instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We are not the first to report findings partly inconsistent with the notion of (the specificity of) the broader phenotype of autism (O'Hanrahan et al 1999;Szatmari et al 1995). Nevertheless, some methodological issues concerning the choice of instruments and design applied in this study should be discussed.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We are not the first to report findings partly inconsistent with the notion of (the specificity of) the broader phenotype of autism (O'Hanrahan et al 1999;Szatmari et al 1995). Nevertheless, some methodological issues concerning the choice of instruments and design applied in this study should be discussed.…”
Section: Discussionmentioning
confidence: 78%
“…Despite early empirical studies (e.g. Cox, Rutter, Newman & Bartak, 1975) and a more recent one (O'Hanrahan, Fitzgerald & O'Reagan, 1999), most investigations since the later 80s also found personality peculiarities in parents of children with autism. For instance, Wolff, Narayan and Moyes, (1988) blindly interviewed parents of children with autism and non-autistic mentally retarded children.…”
Section: Introductionmentioning
confidence: 94%
“…This procedure requires independence of units of analysis. Therefore, for research that reported two outcomes for the same group of participants, and the two outcomes fitted the same psychiatric category as defined in our study (e.g., O'Hanrahan, Fitzgerald, & O'Regan, 1999), we calculated a combined effect size for the two measures by averaging them, and treated this combined effect size as the study's outcome. The two authors independently coded every effect size on each of the six potential moderator variables.…”
Section: Statistical Data and Analysesmentioning
confidence: 99%
“…In testing fourth study hypothesis, comparison of regression analysis results between the two groups of mothers showed that neuroticism plays the most important role in predicting the general health in both groups of mothers (Table 2). Findings of some studies indicated that experiencing challenges related to long-term taking care of children with ID may lead to emergence of special sorts of personality characteristics in the mothers of these children (Koegel et al 1983;Wolff et al 1988;O'Hanrahan et al 1999).…”
Section: Discussionmentioning
confidence: 99%